Effectiveness of the deep and comprehensive Free Trade Area: A structural gravity model approach - Tskhomelidze, Elene (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
Based on the gravity model of international trade, this article examines the ex-post impact of the Deep and Comprehensive Free Trade Area (DCFTA) on integration between Georgia, Moldova, and Ukraine with the European Union. We evaluate the welfare outcome of trade creation and trade diversion effects, compare the results of individual countries and identify differences between them. Additionally, the article evaluates the general effectiveness of the DCFTA as an instrument for trade integration. According to the structural gravity model estimations, as a result of the DCFTA, EU-Georgia trade increased by approximately 18%. In the case of EU-Moldova trade, the DCFTA impact is statistically less significant, around 9%. While DCFTA in Ukraine has a negligible effect on trade with European Union. The agreement brings welfare gains only in the case of Georgia. Generally, the average impact of the DCFTA on trade with the EU is positive but statistically insignificant for the region. The results are very different for each country.